Debating the Historicity of the Qur’an: Between Revisionist-Skeptical and Dialogical-Academic Approaches - Aini, Adrika Fithrotul; Zulfikar, Eko; Masuwd, Mowafg (Canonia Religia, 2025)
Western scholars’ studies on the historicity of the Qur’an have been ongoing since the 12th century to the present day. In their development, some of these studies tend to undermine Islam by employing source criticism and tradition criticism to cast doubt on the authenticity of the Qur’an in early Islamic history. This article aims to examine the debate between revisionist-skeptical and academic-dialogical groups regarding the historicity of the Qur’an. Using qualitative-descriptive methods and critical data analysis, this article finds that studies conducted by revisionist-skeptical scholars such as Abraham Geiger and John Wansbrough view the Qur’an as an imitative text of previous texts and parallel to the Hadith. However, the studies of these revisionist-skeptical scholars are countered by Angelika Neuwirth and Fred M. Donner, as part of the academic-dialogical group. They reject and refute this view by pointing out methodological weaknesses and ideological biases that lead to erroneous conclusions by the revisionists. It is due to initial assumptions based on a negative perspective and a polemical-apologetic attitude towards Islam. They offer a more open and positive approach to Islam. The theoretical implications of these two major schools of thought demonstrate that the initial paradigm for viewing the Qur’an significantly influences the results and direction of research. This article contributes to enriching the study of Orientalism by opening up a more objective, constructive, and relevant scientific dialogue for the development of Qur’anic studies in the contemporary era.